Reconceptualizing The Role of Teachers in Inclusive Education for Early Childhood: Adaptive Pedagogy in Developing the Potential of Children with Special Needs - Purnamasari, Nia Indah; Azis, Abd.; AR, Zaini Tamin; Ardhan, Muhammad Nauliya (WALADI, 2024)
Inclusive education emphasizes equal access and learning opportunities for all children, including those with special needs. In the context of Early Childhood Education (ECE), inclusive education becomes even more crucial, as this period represents a critical phase in children's development. Teachers play a central role in creating a welcoming, adaptive, and supportive learning environment for all students. This article is based on a review of relevant literature provides an in-depth examination of teachers’ roles in inclusive ECE, covering the identification of children's individual needs, the implementation of responsive teaching strategies, and collaboration with parents and professionals. Various challenges faced by teachers in managing inclusive classrooms—such as limited training, inadequate resources, and emotional readiness—are also comprehensively analyzed. This study recommends differentiated instruction, cooperative learning approaches, and the integration of assistive technology to enhance the effectiveness of inclusive education. With the support of appropriate policies, teacher competency development, and the active involvement of all stakeholders, inclusive education can serve as a strong foundation for fostering a more equitable and inclusive developmental environment for children.